Spatial and seasonal patterns of water isotopes in northeastern German lakes - B. Aichner; D. Dubbert; C. Kiel; K. Kohnert; I. Ogashawara; A. Jechow; A. Jechow; S.-F. Harpenslager; F. Hölker; J. C. Nejstgaard; H.-P. Grossart; H.-P. Grossart; et al. (Earth System Science Data, 2022)
Water stable isotopes (δ18O and δ2H) were analyzed in samples collected in lakes, associated with riverine systems in northeastern Germany, throughout 2020. The dataset (Aichner et al., 2021; https://doi.org/10.1594/PANGAEA.935633) is derived from water samples collected at (a) lake shores (sampled in March and July 2020), (b) buoys which were temporarily installed in deep parts of the lake (sampled monthly from March to October 2020), (c) multiple spatially distributed spots in four selected lakes (in September 2020), and (d) the outflow of Müggelsee (sampled biweekly from March 2020 to January 2021). At shores, water was sampled with a pipette from 40–60 cm below the water surface and directly transferred into a measurement vial, while at buoys a Limnos water sampler was used to obtain samples from 1 m below the surface. Isotope analysis was conducted at IGB Berlin, using a Picarro L2130-i cavity ring-down spectrometer, with a measurement uncertainty of <0.15 ‰ (δ18O) and <0.0 ‰ (δ2H). The data give information about the vegetation period and the full seasonal isotope amplitude in the sampled lakes and about spatial isotope variability in different branches of the associated riverine systems.